Kehadiran Kyai sebagai Penceramah dalam Acara Walimah Al- Ursy - Kalamiah, Moh. Jeweherul; Ash Shiddiqi, Hasbi; Safithri, Awaliya (UNIVERSITAS BONDOWOSO, 2023)
This study aims to explore the urgency of the presence of kyai as a speaker in the walimah al-‘ursy (wedding reception) and its impact on the formation of a sakinah family. The research method used is qualitative with a descriptive-analytical approach. Primary data were obtained through interviews with kyai, religious figures, and the bride and groom, as well as secondary data from literature studies and fiqh books. Data analysis was carried out qualitatively to identify the role of kyai in providing advice and guidance during the wedding walimah. The results of the study indicate that the presence of kyai in the walimah al-‘ursy plays a significant role in strengthening the spiritual dimension of marriage. Kyai provides valuable advice on the nature of marriage according to Islamic teachings, such as the importance of loyalty, mutual respect, and responsibility in the family. This advice is not only beneficial for the bride and groom, but also provides guidance for guests about household life according to sharia. Kyai also helps create a peaceful and harmonious atmosphere, and strengthens social ties among family members and the community. The significance of this study lies in the understanding that the presence of a kyai not only enriches the spiritual meaning of marriage but also serves as a link between customs and religious teachings, and strengthens social solidarity. Although not explicitly required in the Shari'a, this tradition is considered to provide great benefits for the bride and groom, their families, and society as a whole, making it an important element in wedding celebrations in Muslim communities.